Professionally packaging your power in the supervisory relationship - Frank Delano; Jill C. Shah (Scottish Journal of Residential Child Care)
This article will look at the dynamic of 'power' in the supervisory relationship. It will discuss the way power is structured in the relationship and the impact it has on both parties. It will look at the ethical responsibility of supervisors to be aware of their power and to wield the power thoughtfully with supervisees. It will address the temptation for both parties to 'play games' related to power, and the impact power has on other aspects of the relationship. The article will look at how both supervisor and supervisee can best balance the power involved to allow for the most productive relationship and to enhance the quality of service to children and families.